2011
DOI: 10.1097/gme.0b013e31821b82ee
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms among healthy, middle-aged Omani women as assessed with the Menopause Rating Scale

Abstract: Omani women were found to exhibit highly atypical symptoms of menopause. Increased severity of symptoms was found to be related to age, advanced stage of menopause, and lower educational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 54 publications
4
27
0
5
Order By: Relevance
“…These findings were also noted by Rahman et al (2010) [30] emphasized that the frequency of sexual problems, bladder problems and vaginal dryness were experienced mainly by premenopausal and postmenopausal group of women and it was also significant statistically in comparison to other menopausal status. The most prevalent psychosocial symptom in the present study was; poor memory that agrees with results of many studies, which indicated that the most common and severe symptom that was reported by women was poor memory [25,31,32] . These contradict with the results of the study done by Kalahroudi MA etal.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings were also noted by Rahman et al (2010) [30] emphasized that the frequency of sexual problems, bladder problems and vaginal dryness were experienced mainly by premenopausal and postmenopausal group of women and it was also significant statistically in comparison to other menopausal status. The most prevalent psychosocial symptom in the present study was; poor memory that agrees with results of many studies, which indicated that the most common and severe symptom that was reported by women was poor memory [25,31,32] . These contradict with the results of the study done by Kalahroudi MA etal.…”
Section: Discussionsupporting
confidence: 82%
“…This contradicted with the study done by Kalahroudi MA etal (2012) [33] reported that menopausal symptoms had a significant association with working status, educational level, exercise activity, exercise frequency and duration of menopause. Several studies have shown that women who had longer education, reported milder menopausal symptoms [39,32] . But one study in Taiwan showed that educated women had more menopausal symptoms compared to less-educated women [35] .…”
Section: Discussionmentioning
confidence: 99%
“…8, 14 The drastic increase in the severity and prevalence of some vasomotor and sexual symptoms, such as hot flashes, sweating, and vaginal dryness, may be explained by estrogen deficiency in menopause. 8 In particular, vasomotor symptoms and vaginal dryness are specifically linked to hormonal changes in the menopausal transition. 14 Some symptoms are not restricted to the perimenopausal and postmenopausal stages.…”
Section: Discussionmentioning
confidence: 99%
“…During menopause, women experience symptoms such as hot flashes, night sweats, impaired memory, depressive symptoms, sleep disturbance, vaginal dryness, urogenital atrophy, bone loss, joint pain, fatigue, headache, weight gain, diminished sexual function, decreased libido, and loss of skin elasticity. 1,[7][8][9][10][11][12] Although most symptoms are not life-threatening, they may have a negative impact on the quality of life (QOL) of many women. 2,3,9,13 Age, sociodemographic characteristics (eg, income, education, and race/ethnicity), chronic conditions, psychosocial and lifestyle factors, and menopause status are important determinants of the prevalence and severity of menopause symptoms.…”
mentioning
confidence: 99%
“…MRS was used to evaluate the symptoms of post-menopausal women in three dimensions: somatovegetative subscales (including hot flushes, heart discomfort, sleep problems and joint and muscular discomfort), psychological subscales (including depressive mood, irritability, anxiety and physical and mental exhaustion), and urogenital subscales (including sexual problems, bladder problems and dryness of vagina) 9) . There were 11 self-reported questions which were scored on a 5-point ordinal score ranging from 1 (no symptom) to 5 (symptoms are very severe).…”
Section: Methodsmentioning
confidence: 99%